2020
DOI: 10.1021/acs.analchem.9b05199
|View full text |Cite
|
Sign up to set email alerts
|

Ratiometric Fluorescent Quantum Dot-Based Biosensor for Chlorothalonil Detection via an Inner-Filter Effect

Abstract: A new sensitive sensor for detecting chlorothalonil (CHL) based on the inner-filter effect (IFE) between gold nanoparticles (AuNPs) and ratiometric fluorescent quantum dots (RF-QDs) was developed. Here, RF-QDs were designed by two different color CdTe QDs. Based on the IFE, the AuNPs can quench the fluorescence of the RF-QDs. Because of the electrostatic attraction between protamine (PRO) and the AuNPs, the PRO can restore fluorescence effectively. Papain (PAP) can easily hydrolyze PRO and causes the quench of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(30 citation statements)
references
References 36 publications
0
30
0
Order By: Relevance
“…As indicated by Chaves et al (2008), the detection limits of chlorothalonil and its degradation products in soil and water were determined to be in the range of 1 and 0.1 µg/L for the LC and GC methods, respectively. A ratiometric fluorescent quantum dot-based biosensor previously synthesized by Sheng et al (2020) was reported to detect chlorothalonil in the range of 0.34-2320 ng/mL. Although the detection limit of chlorothalonil by using SERS method developed in this study was relatively high, maximum residue limits for pesticides in food) requirements, the maximum residue concentration of chlorothalonil in foods was established to be 0.1 ~ 5 ppm according to the Chinese national food safety standard (GB 2763(GB -2014.…”
Section: Resultsmentioning
confidence: 99%
“…As indicated by Chaves et al (2008), the detection limits of chlorothalonil and its degradation products in soil and water were determined to be in the range of 1 and 0.1 µg/L for the LC and GC methods, respectively. A ratiometric fluorescent quantum dot-based biosensor previously synthesized by Sheng et al (2020) was reported to detect chlorothalonil in the range of 0.34-2320 ng/mL. Although the detection limit of chlorothalonil by using SERS method developed in this study was relatively high, maximum residue limits for pesticides in food) requirements, the maximum residue concentration of chlorothalonil in foods was established to be 0.1 ~ 5 ppm according to the Chinese national food safety standard (GB 2763(GB -2014.…”
Section: Resultsmentioning
confidence: 99%
“…These nanomaterial-based ratiometric fluorescent biosensors can be used for the precise detection of a variety of targets including pesticides, proteins, nucleic acids, and small molecules. Moreover, they have also been used for direct visualization of the target analyte with the naked eye, as well as in vitro and in vivo imaging [ 32 , 33 , 34 , 35 , 36 ]. The recent developments in the design and application of nanomaterial-based ratiometric biosensors for fluorescence sensing and cell imaging are reviewed in this section.…”
Section: Nanomaterial-based Ratiometric Fluorescent Biosensorsmentioning
confidence: 99%
“…The established sensing platform exhibits a wider linear range (0.34–2320 ng/mL) for CHL than that of single color QDs. Furthermore, the limit of detection for CHL is achieved as low as 0.0017 ng/mL [ 36 ]. However, the hybrid nanosensors may encounter the problem of uneven local concentration, which can affect the sensitivity and accuracy.…”
Section: Nanomaterial-based Ratiometric Fluorescent Biosensorsmentioning
confidence: 99%
See 2 more Smart Citations